Reatividade cardiovascular ao stress social em situação experimental - Novaes, Miralda Emannuel (Revista de Ciências Médicas, 2005)
Objective This study tested the hypothesis that the stress created by social interactions could increase cardiovascular reactivity and that the magnitude of this increase would depend on whether the interaction offers social support or if it presents a social conflict. Methods The finger blood pressure and heart rate of 58 subjects were recorded continuously before, during and following a structured interview and a role playing task, involving socially stressful interactions between the subjects and a confederate. The twenty-four-hour ambulatory cardiovascular activity was also monitored for ali the subjects in their natural environment. The participants were divided into two groups according to the mean ambulatory arterial blood pressure. Results The blood pressure increased during the role-playing task, and to a lesser extent, during the interview, with no sustained increases in heart rate. Subjects with higher ambulatory blood pressure and Negro subjects did not show greater blood pressure reactivity than subjects with lower ambulatory blood pressure or Caucasian subjects. Women showed greater heart rate changes as compareci to men during scenes that involved social conflict and Caucasian men showed greater heart rate reactivity as compareci to Negro men during social challenge. Conclusion These findings indicate that socially stressful situations may represent a different kind of stressar and suggest the need for further research to directly compare responses to social and mental challenges.